2017
DOI: 10.1007/s40899-017-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Web-based global inventory of managed aquifer recharge applications

Abstract: Managed aquifer recharge (MAR) is being successfully implemented worldwide for various purposes: to increase groundwater storage, improve water quality, restore groundwater levels, prevent salt water intrusion, manage water distribution systems, and enhance ecological benefits. To better understand the role of MAR in sustainable water management and adaptation to climate and land use change, about 1200 case studies from 62 countries were collected and analyzed with respect to historical development, site chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 3 publications
(3 reference statements)
0
76
1
1
Order By: Relevance
“…A recently published global MAR inventory shows that these are also the two most common MAR techniques applied worldwide [15,21]. However, the comparison of the global MAR inventory with this study reveals that spreading methods are the most common MAR techniques worldwide whereas most of the modeling studies identified were conducted for well, shaft and borehole recharge.…”
Section: Modeled Managed Aquifer Recharge Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…A recently published global MAR inventory shows that these are also the two most common MAR techniques applied worldwide [15,21]. However, the comparison of the global MAR inventory with this study reveals that spreading methods are the most common MAR techniques worldwide whereas most of the modeling studies identified were conducted for well, shaft and borehole recharge.…”
Section: Modeled Managed Aquifer Recharge Methodsmentioning
confidence: 72%
“…Well Despite the apparent simplicity of MAR approaches and their large implementation worldwide [15], the complexity of site-specific hydrogeological conditions and the processes occurring at various scales combined with different objectives require a very good understanding of the system's response to the proposed measures. The characterization of the system including heterogeneities such as preferential flow paths is best investigated by field experiments, e.g., [16,17].…”
Section: Techniques Referring Primarily To Getting Water Infiltratedmentioning
confidence: 99%
See 1 more Smart Citation
“…MAR, previously known as artificial recharge [1], is the purposeful recharge of water to aquifers for reuse and/or environmental benefit [1][2][3][4]. Aquifers are permeable geological strata that contain water and are normally replenished naturally by rain permeating through soil and rock or by infiltration from lakes and rivers.…”
Section: Use Of Mar In Urban Water Managementmentioning
confidence: 99%
“…Other classifications of MAR types also exist e.g., [3,4]. There are a large number and growing variety of methods used for MAR internationally e.g., [4].…”
Section: Types Of Marmentioning
confidence: 99%